N-Terminal Pro-B–Type Natriuretic Peptide Is Related to Retinal Microvascular Damage: The Rotterdam Study. Issue 8 (August 2016) - Mutlu, Unal; Ikram, M. Arfan; Hofman, Albert; de Jong, Paulus T.V.M.; Klaver, Caroline C.W.; Ikram, M. Kamran
Abstract : Objective—: N-terminal pro-B–type natriuretic peptide (NT-proBNP) is a marker of cardiac dysfunction and has been linked to various indices of large vessel disease. However, it remains unclear whether NT-proBNP also relates to microvascular damage. In a community-dwelling population, we studied the association between NT-proBNP and retinal microvascular damage. Approach and Results—: From the population-based Rotterdam Study, we included 8437 participants (mean age 64.1 years and 59% women) without a history of cardiovascular disease, with NT-proBNP data and gradable retinal images. NT-proBNP serum levels were measured using an immunoassay. Retinopathy signs, that is, exudates, microaneurysms, cotton wool spots, and dot/blot hemorrhages, present on fundus photographs were graded in the total study population; retinal vascular calibers, that is, arteriolar and venular calibers, were semiautomatically measured in a subsample (n=2763) of the study population. We conducted cross-sectional analyses on the association between NT-proBNP and retinal microvascular damage using logistic and linear regression models, adjusting for age, sex, and cardiovascular risk factors. We found that NT-proBNP was associated with the presence of retinopathy (adjusted odds ratio [95% confidence interval] per SD increase in natural log-transformed NT-proBNP: 1.14 [1.03–1.27]). We also found that higher NT-proBNP was associated with narrower arteriolar calibers (adjusted mean difference in arteriolar caliber per SD increase in natural log-transformed NT-proBNP: −0.89 µm [−1.54 to −0.24]). This association remained unchanged after excluding participants with retinopathy signs. Conclusions—: In participants free of clinical cardiovascular disease, higher levels of NT-proBNP are associated with retinal microvascular damage, suggesting a potential role for NT-proBNP as marker for small vessel disease. Abstract : Supplemental Digital Content is available in the text.